Factors influencing work-family conflict among dual-career couples: a research framework - Krishnan, Anusha Ratha; Alias, Siti Noormi; Omar, Zoharah (Human Resource Management Academic Research Society, 2020)
The purpose of this conceptual paper is to examine the factors influencing work-family conflict among dual-career couples. This study based on an extensive review of past research on work-family conflict among dual-career couples. Total 150 items sourced from the literature both from quantitative and qualitative were used in the analysis, of which about 10 percent was from Asia and the rest from Western countries from 1985 to 2020. However, 60 per cent of them were use in this analysis. The paper offers a number of propositions that explains the proposed model of work-family conflict. Future researches are recommended to test and validate the framework to provide empirical evidence. Upon model validation, the paper can offer practical interventions for human resource development (HRD) practitioners to help dual-career couples in managing work-family conflict issue. The paper proposes the relationship between organization social support, time-management, types of dual-career couples and work-family conflict among dual-career couples. Besides that, this paper also theorizes work-family conflict among dual-career couples by integrating the theory of conservation of resource and gender role theory. The research contributes to literature in work-family and HRD.